The chasm of care: Where does the mental health nursing responsibility lie for the physical health care of people with severe mental illness? - Wynaden, Dianne; Heslop, B.; Heslop, K.; Barr, L.; Lim, E.; Chee, G.; Porter, J.; Murdock, J. (Wiley-Blackwell Publishing Asia, 2016)
The poor physical health of people with a severe mental illness is well documented and health professionals' attitudes, knowledge and skills are identified factors that impact on clients' access to care for their physical health needs. An evaluation was conducted to determine: (i) mental health nurses' attitudes and beliefs about providing physical health care; and, (ii) the effect that participant demographics may have on attitudes to providing physical health care. It was hypothesized that workplace culture would have the largest effect on attitudes. Nurses at three health services completed the "Mental health nurses' attitude towards the physical health care of people with severe and enduring mental illness survey" developed by Robson and Haddad (2012). The 28-item survey measured: nurses' attitudes, confidence, identified barriers to providing care and attitudes towards clients smoking cigarettes. The findings demonstrated that workplace culture did influence the level of physical health care provided to clients. However, at the individual level, nurses remain divided and uncertain where their responsibilities lie. Nursing leadership can have a significant impact on improving clients' physical health outcomes. Education is required to raise awareness of the need to reduce cigarette smoking in this client population.